2008
DOI: 10.1260/174795408785100716
|View full text |Cite
|
Sign up to set email alerts
|

Anxiety and Coping of Hungarian National Ice Hockey Players

Abstract: The purpose of this study was to identify those major psychological factors that affect ice hockey performance. The exploration of the differences in CSAI-2, ACSI-28 and STPI-Y psychometric measures targeted the adult national team members and the U-18 age-group of ice hockey players in Hungary. U-18 (n = 27) and adult national ice hockey players (n = 25) filled out the tests during a training camp before international preliminary round matches. It was found that State Anxiety, Cognitive Anxiety and Somatic A-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0
3

Year Published

2012
2012
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 14 publications
1
12
0
3
Order By: Relevance
“…In relation to player age also influencing emotional experiences, young players have been reported to experience higher anxiety states, be more sensitive to other stressors, and have fewer coping skills than older players (Géczi, Bognár, Tóth, Sipos, & Fügedi, 2008). Géczi et al (2008) showed that levels of anxiety and anger differed between youth and adult players during an ice hockey training camp. The authors also found that youth players were more anxious and angry compared with adult players who were better able to cope with their emotions in critical moments.…”
Section: Individual Characteristicsmentioning
confidence: 99%
“…In relation to player age also influencing emotional experiences, young players have been reported to experience higher anxiety states, be more sensitive to other stressors, and have fewer coping skills than older players (Géczi, Bognár, Tóth, Sipos, & Fügedi, 2008). Géczi et al (2008) showed that levels of anxiety and anger differed between youth and adult players during an ice hockey training camp. The authors also found that youth players were more anxious and angry compared with adult players who were better able to cope with their emotions in critical moments.…”
Section: Individual Characteristicsmentioning
confidence: 99%
“…One of the important factors of successful performance in competition is ability to remain calm in stressful situations (Géczi et al, 2008;Smith et al, 1995). Our research showed that ice hockey players with a high level of the self-esteem and low level of the anxiety have a good psychological resilience and know to quickly bounce back from mistakes or setbacks.…”
Section: Discussionmentioning
confidence: 69%
“…At present, there has not been a single study either evaluating its relationship between anxiety or selfesteem and coping strategies to manage stress in sport. There were some studies carried out earlier by Young and Knight (2014) in risk sport or Vidic et al (2017) in basketball but these studies were only focused on investigating the level of the coping strategies to manage stress or the differences in mental skills between experienced and less experienced athletes (Géczi et al, 2008). However, there has not been a study investigating other factors which may have relationships with coping strategies to manage stress.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations